2021
DOI: 10.1002/art.41777
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Anticoagulant Single Positivity During the Acute Phase of COVID‐19 Is Not Associated With Venous Thromboembolism or In‐Hospital Mortality

Abstract: Objective The clinical relevance of antiphospholipid antibodies (aPLs) in COVID‐19 is controversial. This study was undertaken to investigate the prevalence and prognostic value of conventional and nonconventional aPLs in patients with COVID‐19. Methods This was a multicenter, prospective observational study in a French cohort of patients hospitalized with suspected COVID‐19. Results Two hundred forty‐nine patients were hospitalized with suspected COVID‐19, in whom COVID‐19 was confirmed in 154 and not confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 41 publications
5
35
0
2
Order By: Relevance
“…Univariate analysis did not show any association between LA positivity and higher risk of venous thromboembolism events or in-hospital mortality. Unadjusted and adjusted (to CRP, age and sex) Kaplan–Meier survival curves according to LA positivity confirmed the absence of association with venous thromboembolism events or in-hospital mortality [ 44 ].…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 92%
See 1 more Smart Citation
“…Univariate analysis did not show any association between LA positivity and higher risk of venous thromboembolism events or in-hospital mortality. Unadjusted and adjusted (to CRP, age and sex) Kaplan–Meier survival curves according to LA positivity confirmed the absence of association with venous thromboembolism events or in-hospital mortality [ 44 ].…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 92%
“…However, their pathogenicity and relevance need further examination in future studies, as several diseases including infectious ones, may be associated with transient LA, making their clinical relevance in COVID-19 controversial. Gendron et al investigated the prevalence and prognostic value of conventional and non-conventional APA in COVID-19 patients in a prospective observational French cohort of patients hospitalized for COVID-19 suspicion [ 44 ]. 249 patients were hospitalized for suspected COVID-19, including 154 with confirmed COVID-19 and 95 not confirmed.…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 99%
“…The relationship of LA with mortality and thromboembolic phenomena in COVID-19 infection remains unclear. In a recent cohort of 154 patients diagnosed with COVID-19, LA was frequently present (60.9%), but no relationship with thromboembolic risk and/or in-hospital mortality was observed [16] . The aim of the present study was to determine the prevalence of LA at diagnosis and six months after discharge, in order to estimate its impact on mortality and thrombosis in a prospective observational cohort of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 92%
“…A review of these studies, however, nevertheless lends itself to several key observations. Some have found no consistent association of antiphospholipid antibodies and thrombosis or disease severity [46,49,51,53,64,69,71]. Whether detected at the time of first patient presentation or shortly thereafter, such antibody status is time-accrued, maximizes in over 1 month after infection onset, and tends to be transient [49,68,70].…”
Section: Antiphospholipid Antibodies and Covid-19 Infectionmentioning
confidence: 99%
“…Among patients with lupus anticoagulant, one study of critically ill patients found an association of IgM anticardiolipin antibodies with thrombosis [70]. Antibodies to phosphatidyl serine/prothrombin complex and/or prothrombin appear to be much less common in some but not all studies [68,69,73]. Zuo et al assessed purified immunoglobulin from such patients and found it to promote venous thrombosis in a murine model [67].…”
Section: Antiphospholipid Antibodies and Covid-19 Infectionmentioning
confidence: 99%